ANALYSIS OF THE ROLE OF LEGISLATION AND REGULATIONS IN ORGANIZING GOVERNMENT HOSPITAL MANAGEMENT POLICIES IN THE ERA OF NATIONAL HEALTH SYSTEM TRANSFORMATION (INTERNATIONAL SEMINAR, 2025)
This research aims to examine the role of legislation and regulations in organizing government hospital management policies in the era of national health system transformation. The method used is normative with a literature study approach from various recent books and journals that review legal aspects, public policy, and health system reform in Indonesia. The results of the analysis show that legislation and regulations serve as the main foundation in the formation of government hospital management policies to be able to adapt to the ongoing changes in the national health system. Policies structured through laws and regulations strengthen the governance, transparency, and accountability of government hospitals. Regulations also help harmonize the interests of stakeholders and support the implementation of quality healthcare standards. Regulatory challenges arise from the need for rapid adjustment to technological developments and increasing demands for public services, so strengthening the legal system and supervision is a crucial aspect to ensure the success of this transformation.